2002
DOI: 10.1016/s0014-5793(02)02333-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of SmpB protein in trans‐translation

Abstract: The function of SmpB protein in the trans-translation system was evaluated using the well-defined cell-free translation system consisting of purified ribosome, alanyl-tRNA synthetase and elongation factors. The analysis showed that SmpB protein enhances alanine-accepting activity of tmRNA and that SmpB protein and tmRNA are sufficient to complete the transtranslation process in the presence of translational components. Moreover, SmpB is indispensable in the addition of tag-peptide onto ribosomes by tmRNA. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 20 publications
(31 reference statements)
1
69
0
Order By: Relevance
“…In vitro trans-translation system to evaluate peptidyl transfer to alanyl-tmRNA and translation of the resume codon on tmRNA Several in vitro trans-translation systems have been developed to evaluate tag-peptide synthesis using cell extracts from E. coli or peptidyl transfer from peptidyl-tRNA to alanyl-tmRNA (the first step) using translation and trans-translation factors from E. coli (Shimizu and Ueda 2002;Asano et al 2005). In the present study, we used the system of Asano et al (2005) and extended it to an in vitro system to evaluate two steps of trans-translation, not only the first step but also translation of the resume codon on tmRNA (the second step).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro trans-translation system to evaluate peptidyl transfer to alanyl-tmRNA and translation of the resume codon on tmRNA Several in vitro trans-translation systems have been developed to evaluate tag-peptide synthesis using cell extracts from E. coli or peptidyl transfer from peptidyl-tRNA to alanyl-tmRNA (the first step) using translation and trans-translation factors from E. coli (Shimizu and Ueda 2002;Asano et al 2005). In the present study, we used the system of Asano et al (2005) and extended it to an in vitro system to evaluate two steps of trans-translation, not only the first step but also translation of the resume codon on tmRNA (the second step).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, SmpB is thought to be a key molecule essential for trans-translation. It binds the tRNA-like domain (TLD) to perform multiple functions in the processes of trans-translation, recruitment of tmRNA to the stalled ribosome (Karzai et al 1999;Hanawa-Suetsugu et al 2002), enhancement of aminoacylation of tmRNA by alanyl-tRNA synthetase (Barends et al 2001;HanawaSuetsugu et al 2002;Shimizu and Ueda 2002), enhancement of processing of tmRNA (Wower et al 2004), and protection of tmRNA from degradation in the cell (Hanawa-Suetsugu et al 2002;Hong et al 2005). NMR studies have revealed that SmpB is comprised of an antiparallel b-barrel core with three a-helices and C-terminal basic residues that are disordered in solution (Dong et al 2002;Someya et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…5 and 6). The small basic SmpB protein is essential for transtranslation, enhances tmRNA aminaocylation and prevents its degradation 7,8 binds tmRNA 9 and the stalled ribosomes 10 and is required for loading Ala-tmRNA, in complex with EF-Tu 11 onto the empty (or partially empty) A site of the stalled ribosomes. During the past 10 y, a large body of biochemical, genetic and structural data has accumulated on bacterial trans-translation, converging to a reasonably well experimentally supported scenario.…”
Section: The Why and How Of Trans-translation In Bacteriamentioning
confidence: 99%
“…In eubacteria, a trans-translation surveillance is performed by a ribonucleoprotein complex composed of the small protein B (SmpB) and transfermessenger RNA (tmRNA), a specialized RNA with properties of both a tRNA and an mRNA, to provide a key component of the translation quality control pathway. The multifunctional roles of SmpB include alanylation enhancement of tmRNA (Shimizu and Ueda 2002) and association with tmRNA entering the empty A-site of the ribosome (Hanawa-Suetsugu et al 2002). tmRNA-SmpB interacts with translational complexes blocked at the 39-end of defective mRNAs to release stalled ribosomes and target their nascent polypeptides and mRNAs for degradation.…”
Section: Introductionmentioning
confidence: 99%